Marine benthic forms of the Marine Protected Area Capo Caccia-Isola Piana (Sardinia, Italy). Issue 2 (13th November 2018) - De Luca, Mario; Pascucci, Vincenzo; Gazale, Vittorio; Ruiu, Alberto; Massetti, Luca; Cossu, Andrea
ABSTRACT: The great ecological and economic value of the biocenoses of Marine Protected Area 'Capo Caccia-Isola Piana' (MPA) requires a constant monitoring. For this reason, a continuous study of the area producing overlapping maps useful to control in real time the evolution of the biocenoses is necessary. The integrated use of several methodologies, such as Side Scan Sonar, Remote Operating Vehicle and Drone, has allowed us to realize a very detailed map. This paper presents the marine benthic map of the MPA and compares the present situation with that recorded in 2008.